2022
DOI: 10.56093/ijas.v92i3.122732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc nutrition on economic productivity of rice (Oryza sativa) and soil biological properties

Abstract: Based on our findings, it can be concluded that application of Zn in transplanted rice is essential to harvest profitable yield under acidic soils of NEH region of India. Combined application (soil and foliar) was more effective instead of soil or foliar application alone. Successive yield increment of rice was noticed up to the application of Zn 7.5 kg/ha + foliar spray of Zn @0.5% at panicle initiation and booting stages. Thereafter productivity of rice slightly declined with increases of Zn doses in acidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…These results indicate that increasing the application rate of rice straw compost can significantly increase the biological yield of plants. The results of research by Kumar et al (2003) and Bagas (2021) showed that the application of organic fertilizer doses improved rice plants' performance on plant dry weight variables and plant yield components. While Kaya (2018) found that applying straw compost together with NPK fertilizer can increase Nitrogen (N) uptake, independently straw compost can increase soil N and plant yield components.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that increasing the application rate of rice straw compost can significantly increase the biological yield of plants. The results of research by Kumar et al (2003) and Bagas (2021) showed that the application of organic fertilizer doses improved rice plants' performance on plant dry weight variables and plant yield components. While Kaya (2018) found that applying straw compost together with NPK fertilizer can increase Nitrogen (N) uptake, independently straw compost can increase soil N and plant yield components.…”
Section: Resultsmentioning
confidence: 99%